Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1186/s12909-020-02051-2
|View full text |Cite
|
Sign up to set email alerts
|

GP trainees’ perceptions on learning EBM using conversations in the workplace: a video-stimulated interview study

Abstract: Background: To be able to practice evidence-based medicine (EBM) when making decisions for individual patients, it is important to learn how to combine the best available evidence with the patient's preferences and the physician's clinical expertise. In general practice training, these skills can be learned at the workplace using learning conversations: meetings between the supervising general practitioner (GP) and GP trainee to discuss medical practice, selected topics or professional performance. This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Research on interventions for GP supervisors to facilitate and encourage the practice of EBM by their registrars could also be bene cial. Given that discussion sessions between registrars and supervisors are an opportunity for registrars to learn, collaborative learning discussions can be utilised for development and translation of EBM skills into practice while creating a safe, equal and collaborative environment between registrars and supervisor (39). A previous study reported that this approach was useful for promoting EBM (39).…”
Section: Discussionmentioning
confidence: 99%
“…Research on interventions for GP supervisors to facilitate and encourage the practice of EBM by their registrars could also be bene cial. Given that discussion sessions between registrars and supervisors are an opportunity for registrars to learn, collaborative learning discussions can be utilised for development and translation of EBM skills into practice while creating a safe, equal and collaborative environment between registrars and supervisor (39). A previous study reported that this approach was useful for promoting EBM (39).…”
Section: Discussionmentioning
confidence: 99%
“…Within the broader research project to which this study belongs, 19,24 we selected 22 supervisors and their trainees for maximum variation between September 2016 and April 2017 by giving promotional talks and distributing information leaflets during formal educational sessions at the GP training institutes in Antwerp and Ghent (Belgium) and Utrecht (the Netherlands). 25 Since recruitment was more difficult in the Netherlands, convenience sampling was used there.…”
Section: Participants and Samplingmentioning
confidence: 99%
“…A previous study (part of the larger research project to which this study belongs) showed that trainees indeed see these conversations as an opportunity for EBM learning in which they might discuss the supervisor’s experience and the specific local context in light of what the evidence recommends. 19 However, it is unclear whether supervisors see these conversations as an opportunity to learn EBM from their trainee as well. This study explores how supervisors currently perceive their own EBM learning in learning conversations with their trainee.…”
Section: Introductionmentioning
confidence: 99%
“…GPs experience training about mental health which includes awareness of evidence‐based guidelines (Royal College of General Practitioners, 2019 ); however, acquiring knowledge about self‐harm and the self‐harm guidelines is not a mandatory part of core GP training. Systematic review evidence suggests that prior clinical experiences, including the uptake of further training, also influence GPs’ use of guidelines (Zwolsman et al, 2012 ); trainee GPs encounter more clinical uncertainty (Chatterjee et al, 2017 ; Welink et al, 2020 ) and consult guidelines more readily than experienced GPs who are confident making decisions based upon their expertise (Francke et al, 2008 ; Harris et al, 2014 ; Patel et al, 2001 ; Van Dijk et al, 2010 ). There is a mounting patient safety rationale to ensure evidence‐based guidelines for self‐harm are implemented (Carr et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%